Beautiful and ‘Fiery in Spirit’? The Complexity of the Image of Emperor Isaac II Angelos in the History by Niketas Choniates - Cagić, Ana (Studia Ceranea, 2025)
The depiction of Isaac II Angelos in the History of Niketas Choniates, rounded off with the full description of the emperor in the final paragraph of the account on his first reign (1185–1195), is by far the most complex of all imperial portrayals penned by the respectable historian. The outdated, typically negative image of Isaac II in modern historiography is based only on the surface level of Choniates’ intricate historical narrative, which has been analyzed in greater depth only in the more recent studies. As this paper shall hopefully demonstrate, despite of all literary distortion of his personality, Isaac II remains the most realistically represented character in the History, and the most tangible one, embodying the author’s philosophical-anthropological thought on human nature. The aforementioned description represents a set of authentic body features that meet the criteria of the Byzantine (male) beauty ideal, but it possibly connotes additional meaning, thus making the overall portrayal of Isaac II in the History uniquely complete.